2019
DOI: 10.3389/fnmol.2019.00137
|View full text |Cite
|
Sign up to set email alerts
|

Proestrus Differentially Regulates Expression of Ion Channel and Calcium Homeostasis Genes in GnRH Neurons of Mice

Abstract: In proestrus, the changing gonadal hormone milieu alters the physiological properties of GnRH neurons and contributes to the development of the GnRH surge. We hypothesized that proestrus also influences the expression of different ion channel genes in mouse GnRH neurons. Therefore, we performed gene expression profiling of GnRH neurons collected from intact, proestrous and metestrous GnRH-GFP transgenic mice, respectively. Proestrus changed the expression of 37 ion channel and 8 calcium homeostasis-regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 92 publications
(142 reference statements)
0
15
0
Order By: Relevance
“…The most potential neurotransmitter regulators include gammaaminobutyric acid (GABA) (Herbison and Moenter, 2011), glutamate (Iremonger et al, 2010), dopamine (DA) (Liu and Herbison, 2013), norepinephrine (NE) (Hosny and Jennes, 1998), serotonin (Bhattarai et al, 2014), acetylcholine (Ach) (Turi et al, 2008), and histamine (H) (Fekete et al, 1999). The expression of genes encoding for neurotransmitter receptors (Todman et al, 2005) and ion channels (Bosch et al, 2013;Norberg et al, 2013;Vastagh et al, 2019) in GnRH neurons has also been verified. In a recent study, we have reported that several neurotransmitter receptors belonging to the aforementioned systems show differential expression in GnRH neurons of proestrous mice (Vastagh et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…The most potential neurotransmitter regulators include gammaaminobutyric acid (GABA) (Herbison and Moenter, 2011), glutamate (Iremonger et al, 2010), dopamine (DA) (Liu and Herbison, 2013), norepinephrine (NE) (Hosny and Jennes, 1998), serotonin (Bhattarai et al, 2014), acetylcholine (Ach) (Turi et al, 2008), and histamine (H) (Fekete et al, 1999). The expression of genes encoding for neurotransmitter receptors (Todman et al, 2005) and ion channels (Bosch et al, 2013;Norberg et al, 2013;Vastagh et al, 2019) in GnRH neurons has also been verified. In a recent study, we have reported that several neurotransmitter receptors belonging to the aforementioned systems show differential expression in GnRH neurons of proestrous mice (Vastagh et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…T-type Ca 2+ channels (T-channels) can be activated by small depolarizations of the plasma membrane and have been implicated in a variety of physiological processes, including fertilization, neuronal firing, cancer therapy, hormone secretion and muscle fiber development [8][9][10][11][12] . Bijlenga 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cav3.2 may have a role in reproduction since it facilitates the influx of Ca 2+ in mouse oocytes and eggs to maintain Ca 2+ homeostasis during oocyte maturation and post fertilization 38 . The murine Cacna1h gene is also upregulated in the proestrus of the Gonadotropin-releasing hormone (GnRH) neurons 39 . GnRH determines the pattern of secretion of follicle stimulating hormone (FSH) and luteinising hormone (LH) that regulate the endocrine function and gamete maturation of gonads 40 .…”
Section: Discussionmentioning
confidence: 99%